2010
DOI: 10.1088/0004-637x/716/1/198
|View full text |Cite
|
Sign up to set email alerts
|

The Diskmass Survey. I. Overview

Abstract: We present a survey of the mass surface-density of spiral disks, motivated by outstanding uncertainties in rotation-curve decompositions. Our method exploits integral-field spectroscopy to measure stellar and gas kinematics in nearly face-on galaxies sampled at 515, 660, and 860 nm, using the custom-built SparsePak and PPak instruments. A two-tiered sample, selected from the UGC, includes 146 nearly face-on galaxies, with B < 14.7 and disk scale-lengths between 10 and 20 arcsec, for which we have obtained Hα v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
212
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(227 citation statements)
references
References 76 publications
15
212
0
Order By: Relevance
“…Closer galaxies with larger angular sizes will have values of R 25 that are outside the FoV, while the S/N of small (and faint) galaxies will be not enough for most 2D studies. Our study therefore illustrate the importance of the sample selection not only in terms of volume and limiting magnitude, but also the apparent size of galaxies as previous works have shown (e.g., Bershady et al 2010a).…”
Section: Spatially Resolved Propertiessupporting
confidence: 84%
See 1 more Smart Citation
“…Closer galaxies with larger angular sizes will have values of R 25 that are outside the FoV, while the S/N of small (and faint) galaxies will be not enough for most 2D studies. Our study therefore illustrate the importance of the sample selection not only in terms of volume and limiting magnitude, but also the apparent size of galaxies as previous works have shown (e.g., Bershady et al 2010a).…”
Section: Spatially Resolved Propertiessupporting
confidence: 84%
“…Two different sample selections are explored in this work: (1) galaxies extracted from the SDSS DR4 imaging sample brighter than r < 15.75 mag and of redshift 0.005 < z < 0.025 (selection in volume and limiting magnitude) and (2) face-on disk galaxies included in the DiskMass Survey (DMS, Bershady et al 2010a;Verheijen, priv. comm.…”
Section: Samplementioning
confidence: 99%
“…Colina et al (1999) and de Zeeuw et al (2002), such integral-field spectroscopy has provided a wealth of information. In the nearby universe, for instance, observations from the DiskMass survey (Bershady et al 2010) have indicated that late-type galaxies tend to have sub-maximal disks (Bershady et al 2011), while Atlas-3D observations (Cappellari et al 2011a) showed that early-type galaxies frequently have rapidly rotating components (especially in low-density environments; Cappellari et al 2011b). In the more distant universe, integral-field spectroscopic observations have been crucial in establishing the prevalence of high gas-phase velocity dispersions (e.g., Förster Schreiber et al 2009;Law et al 2009Law et al , 2012Wisnioski et al 2015), giant kiloparsec-sized clumps of young stars (e.g., Förster Schreiber et al 2011), and powerful nuclear outflows (Förster Schreiber et al 2014) that may indicate fundamental differences in gas accretion mechanisms in the young universe (e.g., Dekel et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main goals of the DiskMass Survey (DMS; Bershady et al 2010a, hereafter Paper I) is to break the diskhalo degeneracy using stellar and gas kinematics to determine the dynamical mass-to-light ratio of the galaxy disk (Υ dyn ). For a locally isothermal disk…”
Section: Introductionmentioning
confidence: 99%